Smallholder integration into the global shea nut commodity chain in northern Ghana - Wolfram Laube; Martha Adimabuno Awo; Emmanuel Kanchebe Derbile (University of Bonn, Center for Development Research (ZEF), 2017)
The integration of African smallholders into global commodity chains is often portrayed as an engine for rural transformation that will generate broad-based economic growth and help to eradicate poverty. In this vein, in northern Ghana, the production of shea nuts, the fruit of the semidomesticated shea nut tree, which is in high demand in the international confectionary and cosmetic industry, is promoted by government agencies, international donors, non-governmental organizations, and agro-processing companies alike. In their discourses shea nuts become 'women's gold' and the shea industry an engine of poverty reduction. Based on qualitative and quantitative research in the Upper East and Upper West regions of northern Ghana this paper discusses the actual impact and future promises of smallholder integration into the global shea market. The way producers - mainly women from poor rural smallholder households - gain access to nuts and produce and market their crops is described, and the profits derived at different steps of the Ghanaian shea value chain analyzed. The research results show that the sale of shea nuts does provide a welcome source of income for rural women and poor rural households in Northern Ghana at a time of year when resources are scarce. Thus the production and sale of shea nuts helps to mitigate poverty. But the findings also suggest that because of low levels of production, resulting from labor and resource access constraints, as well as exploitative price setting by oligopolistic shea processing companies, the integration into the global shea commodity chain is not a 'game changer' for the producers. It does not have the potential of moving poor rural households out of poverty. This is also reflected in the behavior of rural women who tend to disengage from shea picking when more profitable economic activities such as independent farming, wage labor, or business opportunities arise. Therefore, discourses promoting shea production do not seem to rest on a sober analysis of the socio-economic impact of commodity chain integration, but rather tend to serve political, public relation, and marketing ends.
Keywords: 330; smallholders; global commodity chains; poverty reduction; shea nuts; Northern Ghana